Singapore's protection of minorities: religious freedom and state management - Hedges, Paul (2024)
At a time of heightened Islamophobia and antisemitism in many parts of the world resulting from the Israeli-Hamas war, Minister for Home Affairs and Law, Mr K. Shanmugam, recently stated Singapore’s determination to protect all minorities, especially the Jewish and Muslim communities. This stance is hardly surprising considering Singapore’s no-nonsense and unashamedly tough approach to managing racial and religious harmony among the diverse communities.